Managing of Perceived Passenger Safety in Integrated Transport Hubs in the Metropolis GZM - Iwona KRZYŻEWSKA; Anna ŚMIGLEWICZ (Communications of International Proceedings, 2025)
The article analyzes the management of passengers’ perceived safety at integrated transport hubs within the Metropolis GZM (GZM - Górnośląsko-Zagłębiowska Metropolia). The theoretical section discusses the importance of mobility and accessibility in the context of social integration and passenger inclusion at intermodal hubs. The literature indicates that the perception of safety depends primarily on users’ subjective feelings, with women and older individuals more frequently reporting a higher sense of risk. A quantitative study was conducted at five major transport hubs: Katowice Dworzec, Katowice Sądowa, Chorzów Rynek, Dąbrowa Górnicza, and CP Gliwice (Centrum Przesiadkowe – ang. Transfer Hubs) covering a sample of 265 respondents. The results show that the majority of passengers feel safe (67%), while over 79% do not experience fear of crime. The highest level of perceived safety was recorded at Katowice Sądowa, whereas the lowest was observed at Chorzów Rynek and CP Gliwice. Women and older passengers reported lower levels of perceived safety compared to men and middle-aged respondents. The findings confirm that perceived safety constitutes a key element of the passenger experience and a prerequisite for fair and sustainable mobility. The authors highlight the need to improve lighting, enhance staff visibility, and upgrade signage, particularly at the lowest-rated hubs. The objective of this study is to assess passengers’ perceived sense of safety at five integrated transport hubs within the GZM Metropolis.
Keywords: perceived safety; public transport; Metropolis GZM; integrated transfer nodes